Diversity of mammals and its preferences for the habitats types in the upper Itaya river basin, Peruvian Amazon - Aquino, Rolando (2012)
This report contains information about the diversity of mammals and preferences for habitat types in the upper Itaya river basin. For this purpose, censuses by transect were conducted and supplemented out censuses observations and with hunters interviews information. As a result of the study 48 species were recorded. Greater diversity was recorded in forest of heavily dissected low hill (Bcbfd). On the other hand, 20 species were shared among the three habitat types, while the highest similarity occurred between the forest of heavily dissected low hill (Bcbfd) and the forest of moderately dissected low hill (Bcbmd). Finally, the presence of indicator species as the primary community as Tapirus terrestris, Priodontes maximus, Lagothrix poeppigii and Tayassu pecari, indicate that the conservation status of wildlife in general is intermediate to high level.